Application of PDCA cycle combined with care bundles for patients undergoing continuous renal replacement therapy for sepsis (PDCA循环管理联合集束化护理在脓毒血症患者行连续性肾脏替代治疗中的应用) - HU Qinna (胡琴娜); XU Lingfen (徐玲芬) (Journal of International Translational Medicine Limited, 2022)
Objective To observe the value of PDCA cycle combined with care bundles for patients undergoing continuous renal replacement therapy (CRRT) for sepsis. Methods Totally 75 patients with sepsis requiring CRRT were divided into the control group (n=37) and the observation group (n=38) according to the sequential order of hospital admission. The control group received intensive care and infection control during the CRRT, and the observation group was given care bundles and infection control based on PDCA cycle management. The incidence of catheter-related blood stream infection(CRBSI), duration of CRRT and length of ICU stay were observed and compared between two groups. Results The incidence of CRBSI in the observation group was lower than that in the control group (P＜0. 05). The duration of CRRT and length of ICU stay were shorter in the observation group than those in the control group(P＜0. 05). Conclusion The PDCA cycle combined with care bundles may reduce the risk of CRBSI during the CRRT, which helps to promote successful withdrawal of CRRT and shorten the length of ICU stay. (目的 观察PDCA循环管理联合集束化护理策略在脓毒血症患者连续性肾脏替代治疗(CRRT)中的应用效果。方法 选取在2020年3月-2021年10月医院收治的75例行CRRT的脓毒血症患者为研究对象, 根据入院时间分为对照组37例和观察组38例。治疗期间, 对照组患者接受常规重症护理和感染预防措施, 观察组患者给予PDCA循环管理模式联合集束化护理策略。对比两组患者导管相关血流感染(CRBSI)发生率、CRRT治疗时间、ICU入住时间。结果 观察组CRBSI发生率低于对照组, 差异有统计学意义(P＜0. 05)。观察组患者CRRT诊疗时间和ICU入住时间较对照组短, 差异有统计学意义(P＜0. 05)。结论 PDCA循环管理模式联合集束化护理能降低脓毒血症患者CRRT治疗期间CRBSI发生风险, 有助于患者尽早撤机及缩短患者ICU住院时间。)